The RNA-binding protein TcUBP1 up-regulates an RNA regulon for a cell surface–associated Trypanosoma cruzi glycoprotein and promotes parasite infectivity - Sabalette, Karina Belén (2019)
The regulation of transcription in trypanosomes is unusual. To modulate protein synthesis during their complex developmental stages, these unicellular microorganisms rely largely on post-transcriptional gene expression pathways. These pathways include a plethora of RNA-binding proteins (RBPs) that modulate all steps of the mRNA life cycle in trypanosomes and help organize transcriptomes into clusters of post-transcriptional regulons. The aim of this work was to characterize an RNA regulon comprising numerous transcripts of trypomastigote-associated cell-surface glycoproteins that are preferentially expressed in the infective stages of the human parasite Trypanosoma cruzi. In vitro and in vivo RNA-binding assays disclosed that these glycoprotein mRNAs are targeted by the small trypanosomatid-exclusive RBP in T. cruzi, U-rich RBP 1 (TcUBP1). Overexpression of a GFP-tagged TcUBP1 in replicative parasites resulted in >10 times up-regulated expression of transcripts encoding surface proteins and in changes in their subcellular localization from the posterior region to the perinuclear region of the cytoplasm, as is typically observed in the infective parasite stages. Moreover, RT–quantitative PCR analysis of actively translated mRNAs by sucrose cushion fractionation revealed an increased abundance of these target transcripts in the polysome fraction of TcUBP1-induced samples. Because these surface proteins are involved in cell adherence or invasion during host infection, we also carried out in vitro infections with TcUBP1-transgenic trypomastigotes and observed that TcUBP1 overexpression significantly increases parasite infectivity. Our findings provide evidence for a role of TcUBP1 in trypomastigote stage-specific gene regulation important for T. cruzi virulence.